Respuesta :
Here is the answer:
[tex]A. 3(4)-6+5(4) =12-6+20 =6+20 =26[/tex]
[tex]B.20-3^2(5) = 20-9(5) =20-45 =-25[/tex]. Hope it help!
[tex]A. 3(4)-6+5(4) =12-6+20 =6+20 =26[/tex]
[tex]B.20-3^2(5) = 20-9(5) =20-45 =-25[/tex]. Hope it help!
A: First you multiply the 3(4) to get 12 - 6 + 5(4). Then you multiply the 5(4) to get 12 - 6 + 20. You then subtract the rest to get 6 + 20. Then add and get 26.
B: First you get rid of the exponent and turn 3^2 into 9, and you'll have 20 - 9(5). Then you'll multiply 9(5) to get 45. Lastly you do 20 - 45 and get -25.
A: 26
B: -25